Comparison of Stability of Cetirizine Dihydrochloride in Solid and Liquid Dosage Forms by HPLC Analytical Method - Usman, Dr. Shahnaz (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The objective of the present study was to compare the stability of cetirizine (CTZ) dihydrochloride in different formulations of tablet and syrup dosage form by long-term and accelerated stability studies conducted according to an international conference on harmonization (ICH) guidelines. Materials and Methods: Both the dosage forms were formulated with the help of various excipients. The pharmaceutical analysis was performed for the quality attributes, and both formulations were kept for long-term stability studies at 30 ± 2°C and 65 ± 5 RH for 36th months and 6th months for accelerated stability studies at 40 ± 2°C and 75 ± 5 RH. The estimation of CTZ was done by high-performance liquid chromatography (HPLC) by recommended USP method that was previously calibrated and validated as per the ICH guideline. Results: The content analysis of tablet and syrup formulation was found to be 99.63–97.59% after 36th months of long-term stability conditions, respectively, whereas after completion of 6th months of accelerated stability studies, percentage content was 99.95–98.73%, respectively. Conclusion: It was concluded that CTZ is more stable in tablet dosage form as compared to syrup dosage form. It was also verified that the HPLC analytical method, present in USP, is useful for content analysis of CTZ in tablets and syrup dosage form.